2003
DOI: 10.1051/animres:2003039
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of oleic acid and vitamin E concentrations of bovine milk using dietary supplements of whole rapeseed and vitamin E

Abstract: -With the aim of reducing the degree of saturation and increasing the C18:1 cis fatty acid content of milk fat, the effects of feeding high levels of whole cracked rapeseed to dairy cows was investigated together with the effect of increasing dietary intake of vitamin E on the vitamin E content of milk. Using a 3 × 3 factorial design, 90 Holstein dairy cows were fed one of three levels of whole cracked rapeseed (0 (ZR), 134 (MR) and 270 g·kg -1 diet dry matter (DM) (HR)) in combination with one of three intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 25 publications
4
19
1
Order By: Relevance
“…Milk yield in R was significantly decreased in comparison with S. This is in agreement with e.g. Givens et al (2003) or Solomon et al (2000). On the other hand, Kudrna and Marounek (2006) did not find a difference in milk yield between cows receiving rapeseed cake and extruded soybeans.…”
Section: Discussionsupporting
confidence: 86%
“…Milk yield in R was significantly decreased in comparison with S. This is in agreement with e.g. Givens et al (2003) or Solomon et al (2000). On the other hand, Kudrna and Marounek (2006) did not find a difference in milk yield between cows receiving rapeseed cake and extruded soybeans.…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, the percentage of nutritionally favourable monounsaturated oleic acid (C18:1; OA) increased (P < 0.05) in milk produced using Energol in the diet in comparison with control milk by more than 10 percentage units in each of the recorded stages of lactation (Table 6). These figures correspond with the data of DePeters et al (2001; increase in OA from 15 to 21 g/100 g of milk fat of dairy cows fed the diet with canola oil) or of Loor et al (2002; increase in OA in a similar experiment with canola oil from 16% to 26%), and data of Givens et al (2003), who found an increase in OA content from 18.1% (control) to 40% of the sum of total determined fatty acids in milk of dairy cows fed the diet with whole cracked rapeseed. Rapeseed oil content in the cow's daily ration was nearly 2 kg in the experiment of Givens et al (2003); however, it was only a half of this amount in the present experiment (0.3 kg from Energol and 0.65 kg from 5 kg of the experimental production mixture).…”
Section: Fatty Acid Content In Milksupporting
confidence: 88%
“…Replacing CPO with whole and milled rapeseeds (WR and MR) in the diet had little effect on DM intake, but rapeseed oil reduced (P , 0.05) intake. Givens et al (2003) recorded substantial DM intake reductions in cows fed cracked whole rapeseeds, providing greater amounts of rapeseed oil (1.21 kg/cow per day) than in the present study. A lower intake with diets containing rapeseed oil may reflect the negative effects of unsaturated fatty acids on rumen function (Palmquist, 1994), and if so, suggests that both the WR and MR treatments provided some degree of rumen protection to the constituent oil.…”
Section: Discussioncontrasting
confidence: 52%